2022
DOI: 10.1186/s13213-022-01701-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of soil microbial potassium solubilizers in potassium nutrient availability in soil and its dynamics

Abstract: Background An increase in population has led to a higher demand for food. Meeting up this demand has necessitated the use of chemical fertilizers. However, utilization of these fertilizers has a considerable deleterious effect on the soil, plant, human, environmental sustainability, and only increase the cost and reduced profitability. With these identified problems, there is a need for efficient and sustainable methods regarding managing natural resources to enhance food production. Naturally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…These outcomes suggest that KSB was capable of producing certain acids, either organic or inorganic, which contributed to the breakdown of the potassium aluminum silicate complex and released inorganic K, hence increasing the K content (Meena et al, 2016 ). Olaniyan et al ( 2022 ) described previously that K + secrete organic acids, such as tartaric acid, citric acid, and oxalic acid, to solubilize the mineral K + and make it accessible to plants.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes suggest that KSB was capable of producing certain acids, either organic or inorganic, which contributed to the breakdown of the potassium aluminum silicate complex and released inorganic K, hence increasing the K content (Meena et al, 2016 ). Olaniyan et al ( 2022 ) described previously that K + secrete organic acids, such as tartaric acid, citric acid, and oxalic acid, to solubilize the mineral K + and make it accessible to plants.…”
Section: Discussionmentioning
confidence: 99%
“…Potassium in soil exists in various forms, with a significant portion locked in mineral structures that plants cannot directly use. Soil microorganisms, particularly certain bacteria and fungi, are adapt at transforming this unavailable potassium into accessible forms for plants [ 77 ]. These microorganisms utilize their metabolic capabilities to produce organic acids, which play a central role in potassium solubilization.…”
Section: Soil Macronutrientsmentioning
confidence: 99%
“…Yang and coauthors (2020) found that nitrogen and potassium were the strongest predictors of bacterial community composition out of eight nutrients surveyed. Like soil organic matter, potassium levels in the soil are not only determinants of microbial community composition but microbes also solubilize potassium in soils through the release of organic acids (Olaniyan et al 2022).…”
Section: Plant Height Is An Important Determinant Of Microbial Commun...mentioning
confidence: 99%